The Presentation Structure of Lontang Dance as a Symbolic System in Cultural Communication: A Symbolic Interactionist Study of Ritual Tradition in Purwaraja, Ciamis - Arni Apriani; Asep Wasta; Wan Ridwan Husen; Abdul Khoer Al Gani (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Lontang Dance, a ritual performance from Purwaraja, Ciamis, operates as a medium of cultural communication beyond its aesthetic function. Although prior studies address its symbolic meanings, limited attention has been given to how its performance structure organizes communicative processes. This study examines the presentation structure of Lontang Dance as a symbolic communication system through symbolic interactionism, cultural communication theory, and ethnocoreology. A qualitative focused ethnography was conducted using participant observation, in-depth interviews, and visual documentation, with data analyzed thematically. The findings identify four structural phases opening, core, participatory, and closing each serving distinct communicative roles: spiritual legitimation, embodied value expression, collective interaction, and social redistribution. These phases actively shape how meanings are produced and negotiated among participants. This study offers a novel contribution by positioning performance structure as an operative symbolic communication system, extending symbolic interactionism into the analysis of ritual performance.